2019
DOI: 10.1002/1878-0261.12568
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic, transcriptomic and genetic integrative analysis reveals important roles of adenosine diphosphate in haemostasis and platelet activation in non‐small‐cell lung cancer

Abstract: Lung cancer is the leading cause of cancer-related deaths in the world. The most prevalent subtype, accounting for 85% of cases, is non-small-cell lung cancer (NSCLC). Lung squamous cell carcinoma (LUSC) and lung adenocarcinoma (LUAD) are the most common subtypes. Despite recent advances in treatment, the low 5-year survival rate of NSCLC patients (approximately 13%) reflects the lack of early diagnostic biomarkers and incomplete understanding of the underlying disease mechanisms. We hypothesized that integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Eligible data sets in GEO were selected according to the following criteria and 11 data sets were obtained as of May 2020 (including 268 cases of control samples, 601 cases of lung tumor samples) (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Data sets details are listed in Table 1.…”
Section: Raw Datamentioning
confidence: 99%
“…Eligible data sets in GEO were selected according to the following criteria and 11 data sets were obtained as of May 2020 (including 268 cases of control samples, 601 cases of lung tumor samples) (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Data sets details are listed in Table 1.…”
Section: Raw Datamentioning
confidence: 99%
“…Human lung cancers are widely known highly heterogeneous as revealed by transcriptomic, genomic, epigenomic, and proteomic profiles analysis [ 7 , 25 , 26 ]. In this study, we provide the in vivo evidence showing that cancer cells at the invasive front exhibit a higher level of autophagic flux than cancer cells inside the tumor body do.…”
Section: Discussionmentioning
confidence: 99%
“…Novel drugs that target VEGF, including anti-VEGF antibodies, anti-VEGF receptor antibodies, and small-molecule tyrosine kinase inhibitors, are already available and approved for the treatment of various tumors, including lung cancer. 40 Besides, a large number of downregulated differentially expressed circRNAs have been associated with other tumor signaling pathways, such as platelet activation, 41 MAPK signaling, 42 and RAS signaling. 43 KEGG analysis showed that upregulated and differentially expressed circRNAs were mainly associated with RNA transport and ribosome biogenesis with potential targets for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%